DOI: 10.32657/10356/146978
|View full text |Cite
|
Sign up to set email alerts
|

Biocementation and bioclogging of sand using improved MICP techniques

Abstract: from the Environmental Laboratory for rendering the help on equipment, chemicals, and laboratory testing. I am also grateful to the assistance received from my groupmates Wang Lei, Ye Dawei, and Chen Hao. In addition, I am thankful to my other colleagues, Zhang Dong, and Ruan Shaoqin for their technical support and sharing their experience in laboratory work.Last but not least, I am indebted to my parents for their unceasing support and encouragement. This Ph. D thesis is the outcome of their sacrifice.vi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…The reason for this may be that the medium used for the activation and passaging of the bacteria was de-ionised water, which the Bacillus pasteurii had already adapted to, while the seawater environment is more complicated than the de-ionised water environment, such that the bacteria had to adapt to the environment after entering it, leading to a delay period. 3 ⃝ The overall trend of bacterial liquid concentration was stable after 24 h of incubation. When the seawater gradient domestication tended to be stable, the concentration of the bacterial sap showed a gradual increase with an increase in the domestication gradient; that is, b < c-2 < d-3.…”
Section: Analysis Of the Bacillus Pasteurii Domestication Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The reason for this may be that the medium used for the activation and passaging of the bacteria was de-ionised water, which the Bacillus pasteurii had already adapted to, while the seawater environment is more complicated than the de-ionised water environment, such that the bacteria had to adapt to the environment after entering it, leading to a delay period. 3 ⃝ The overall trend of bacterial liquid concentration was stable after 24 h of incubation. When the seawater gradient domestication tended to be stable, the concentration of the bacterial sap showed a gradual increase with an increase in the domestication gradient; that is, b < c-2 < d-3.…”
Section: Analysis Of the Bacillus Pasteurii Domestication Resultsmentioning
confidence: 92%
“…Comparing different seawater gradients, it was found that, the higher the seawater concentration, the greater the effect on the activity of the bacteria; and, the use of multiple gradients of seawater concentration to domesticate and cultivate Bacillus pasteurii better enabled the bacteria to transition from the de-ionised water environment to the seawater environment, which thus better protected the bacterial urease activity. 3 ⃝ The bacterial urease activity at the end of the multi-gradient culture test with natural seawater under different domestication schemes also slightly differed: when the bacterial concentration tended to be stable, the bacterial urease activity of b was lower than that of c-2 and d-3, while c-2 and d-3 presented alternating urease activities due to the inconsistency in the time period that they arrived at their peaks. The bacterial urease activity did not differ much in general.…”
Section: Analysis Of the Bacillus Pasteurii Domestication Resultsmentioning
confidence: 99%
See 1 more Smart Citation